1994
DOI: 10.1002/1097-4679(199407)50:4<529::aid-jclp2270500408>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

MMPI profiles in PTSD as a function of comorbidity

Abstract: A sample of 135 Vietnam veteran inpatients with combat‐related PTSD was sorted into three groups, depending upon the presence of concurrent psychiatric disorders: Depression (n = 68), Psychosis (n = 31), and Other (n = 36). Pairwise comparisons were made on the MMPI with respect to the validity indicators, clinical scales, four relevant Harris‐Lingoes subscales, the Psychoticism content scale, and the MMPI‐PTSD subscale. Results indicate variations in scale elevations as a function of comorbid diagnosis. Vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…On the basis of this study's findings, domestic violence survivors with and without PTSD appear to have different psychological presentations, and the MMPI-2 appears to accurately reflect these differences. The PK-PTSD supplementary scale also showed sensitivity to PTSD symptoms by generating rates of diagnostic accuracy similar to research reported for Vietnam veterans (see Litze et al, 1991;Talbert et al, 1994). The results of this current study provide preliminary empirical evidence that the PK-PTSD scale may be a useful measure of PTSD in the domestic violence population.…”
Section: Discussionsupporting
confidence: 80%
“…On the basis of this study's findings, domestic violence survivors with and without PTSD appear to have different psychological presentations, and the MMPI-2 appears to accurately reflect these differences. The PK-PTSD supplementary scale also showed sensitivity to PTSD symptoms by generating rates of diagnostic accuracy similar to research reported for Vietnam veterans (see Litze et al, 1991;Talbert et al, 1994). The results of this current study provide preliminary empirical evidence that the PK-PTSD scale may be a useful measure of PTSD in the domestic violence population.…”
Section: Discussionsupporting
confidence: 80%
“…Recent literature (e.g., Talbert et al, 1994) suggests that certain MMPI-2 scales would be most apt to differentiate among the three groups. We limited our selection to nine scales because of the sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, Kenderdine, Phillips, and Scurfield (1992) demonstrated significant differences on the MMPI-PTSD scale among PTSD patients with and without substance abuse, and patients diagnosed only with substance abuse. More recently, Talbert et al (1994) found that patients with PTSD and a second psychiatric illness (psychosis, depression, or other disorder), produced different elevations on MMPI scales. A review by Wise (1996) found that the MMPI 8-2 profile best distinguished PTSD and other psychiatric patients.…”
mentioning
confidence: 99%
“…Peak elevations have often been reported on Scale 2 (Depression; D), measuring depressive symptoms and restricted affect, and Scale 8 (Schizophrenia; Sc), measuring social alienation, difficulties in thinking or concentrating, and possible intrusive symptoms (Lyons & Wheeler-Cox, 1999). These profiles are usually coded as a 2-8 or 28/82 code type (Fairbank, Keane, & Malloy, 1983;Lyons et al, 1988;Orr et al, 1990;Talbert et al, 1994;Wilson & Walker, 1990;Wise, 1996).…”
mentioning
confidence: 99%